Meningkatkan Motivasi Belajar Peserta Didik Kelas 8B pada Materi Sistem Peredaran Darah Manusia Sub Materi Anemia di SMP Muhammadiyah 2 Taman Sidoarjo - Azzahro, Izzah Fatimah; Saputra, Bachtiar Adi (TSAQOFAH, 2024)
The Human Circulatory System material has strong relevance to everyday life, and therefore, understanding the factors that influence motivation to learn this material is essential. Therefore, there is a need for innovation in the form of good practice in learning which is important to share so that it can be used as the best reference or inspiration for fellow teachers who experience the same problems as I experienced, so that it has an impact on improving learning in the classroom. The strategy used to achieve the goal is to carry out learning using the Problem Based Learning (PBL) model. The research results show that the use of media in learning practice is very significant in increasing students' understanding. The students' response to this learning activity was very enthusiastic, because learning was very fun. The media used is very close to students' daily lives so that the material can be easily understood. This can be seen from the results of initial test assessments, attitude assessments, and performance observations. Apart from that, based on the results of student evaluations, with a KKTP of 78 out of 28 students, there are 2 (7%) students who have not achieved the KKTP while 26 (93%) students have achieved the KKTP. In terms of student evaluation, the KKTP data shows satisfactory results. With 78 out of 28 students achieving the KKTP, it can be concluded that the majority of students have achieved the desired competency. Even though there were 2 students who had not yet achieved the KKTP, the overall percentage of students who achieved this competency reached 93%, indicating overall learning success. This evaluation is an indicator that the use of media and the learning approach applied has a positive impact on student competency achievement, as well as increasing students' learning motivation.